Sweet syndrome following Moderna COVID-19 vaccine: A case report. (August 2022) - Pelchat, Frederic; Fournier, Cynthia; Perron, Emilie; Gilbert, Martin; Delisle, Bernard
With the COVID-19 pandemic, vaccines have been administered all around the world probably more than ever. Even though they are considered safe, with such a huge quantity of doses used, many adverse effects including cutaneous ones were reported. We report here the case of a male adult with a history of monoclonal gammopathy of undetermined significance who presented with an extensive cutaneous eruption of indurated erythematous papules and plaques 2 days after receiving his first dose of Moderna COVID-19 vaccine (mRNA-1273 SARS-CoV-2 vaccine). Histopathology was compatible with a histiocytoid Sweet syndrome and history suggested that the vaccine contributed to the eruption.